HOBE: The Danish Hydrological Observatory. Issue 1 (8th November 2018) - Jensen, Karsten H.; Refsgaard, Jens Christian
Abstract : Core Ideas: HOBE provides an experimental catchment infrastructure. Measurements, experiments, and modeling are carried out. A number of research questions are addressed; the primary one is closure of the water balance. The database is available for data sharing. The Danish hydrological observatory was established in 2007 in a catchment in the western part of Denmark representing hydrological conditions in a temperate climate with groundwater‐dominated streamflow. In the catchment, an experimental infrastructure has been established where measurements, experiments, and modeling are performed across a range of spatial and temporal scales. The primary research question is water balance closure at different scales, which has been addressed using improved measurement and modeling methods. In addition, an array of research questions are related to processes in the individual hydrological compartments as well as the interactions between them. We provide here an overview of long‐term monitoring and observation, dedicated observations, experiments, and modeling. An overview of main research findings is also provided. The research has provided new insights into the dynamics of the individual hydrological processes and their interactions. The hydrological fluxes are now determined with greater certainty, and the water balance is better constrained at different spatial scales.